Serum gamma-glutamyl transferase levels affect the prognosis of patients with intrahepatic cholangiocarcinoma who receive postoperative adjuvant transcatheter arterial chemoembolization: A propensity score matching study. (January 2017) - Lu, Zhufeng; Liu, Shuang; Yi, Yong; Ni, Xiaochun; Wang, Jiaxing; Huang, Jinlong; Fu, Yipeng; Cao, Ya; Zhou, Jian; Fan, Jia; Qiu, Shuangjian
Abstract: Background: The postoperative prognosis of patients with intrahepatic cholangiocarcinoma (ICC) is far from satisfactory. Whether postoperative adjuvant transcatheter arterial chemoembolization (TACE) is effective for patients with ICC after R0 liver resection remains controversial. Materials and methods: We retrospectively reviewed the data of 272 patients with ICC who received a radical hepatectomy at our center between 2000 and 2011. After the propensity score of postoperative TACE was calculated, 75 patients who received TACE were matched at a 1:2 ratios with 150 patients who did not receive TACE. Univariate and multivariate Cox analyses were performed to identify the independent predictors of overall survival. Results: The postoperative protective effect of adjuvant TACE was significantly influenced by serum gamma-glutamyl transferase (GGT) levels (P for interaction = 0.026). Postoperative TACE was not a significant predictor of overall survival (hazard ratio = 0.89, P = 0.704) in patients with GGT levels ≤ 54 U/L. Postoperative TACE was a significant predictor of overall survival in patients with GGT levels >54 U/L (hazard ratio = 0.44, P = 0.001). Regarding short-term outcomes, a total of 74 patients (32.9%) had varying degrees of complications, and the majority of these complications were grade I (18.7%) or II (10.2%). Conclusion: The safety of postoperative TACE was validated, and the results suggest that only patients with elevated serum GGT levels will benefit from this treatment following curative liver resection for ICC. Highlights: Adjuvant TACE is safe for patients with ICC after R0 liver resection. Serum GGT levels affect patients' overall survival after adjuvant TACE. Patients with elevated serum GGT levels get survival benefits from adjuvant TACE.